EFFECT OF COMPRESSIVE STRENGTH OF CONCRETE WITH PARTIAL SUBSTITUTION OF FINE AGGREGATES WITH WASTE BAMBOO FIBERS - RAZAK MOHAMADHAN; GALI PRIBADI; LYDIA DARMIYANTI (CV KULTURA DIGITAL MEDIA, 2025)
Concrete consists of cement, sand, gravel and water, with cement being the main binder that affects its quality. However, the increasing cost of raw materials and the environmental impact of lime mining and sand dredging are challenges in construction. To address this, the study proposed the use of bamboo fiber as an environmentally friendly and economical additive. This study tested the variation of 0%, 10%, and 15% pulung bamboo fiber waste on the compressive strength of concrete. The results showed that normal concrete without bamboo fiber had a compressive strength of 452 kN (fc' 26.08 MPa). The addition of 10% bamboo fiber decreased the compressive strength to 404 kN (fc' 23.32 MPa), while the addition of 15% decreased it further to 393 kN (fc' 22.68 MPa). The more bamboo fiber added, the more the compressive strength of the concrete decreased.